The Role of Training and Employee Performance in Department of Public Work and Spatial Planning in Pelalawan Regency with Discipline and Work Motivation as Intervening Variable - Remon Saputra (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2017)
The role training and on employee performance in Departement of Public Works and Spatial Planning in Pelalawan Regency with discipline and work motivation as intervening variable. This research was conducted on Departement of Public Works and Spatial Planning of Pelalawan Regency which aims to know the effect of training, discipline and work motivation variable on employee performance. The population of this research is using cencus technique, which is taken from all employees both civil servants and non civil servants who have attended training for the last 5 (five) years. The analysis used in this research is using WarpPLS analysis technique.The results showed that the training has a significant effect on work discipline and employee work motivation (H1 and H2 are accepted). And While based on the results of testing the effect of training on performance has not significant (H3 is rejected). Thus it can be said that the training does not affect the employee performance through work discipline (H4 is accepted). And indirect testing of training is not proven to have an effect on improving performance through work motivation (H5 is rejected)